Skrining Faktor Risiko Penyakit Kardiovaskuler Pada Pemain Minisoccer Dewasa - Wilda Fauzia; Ana Khumaeroh (Cv. Utility Project Solution, 2023)
The prevalence of cardiovascular disease in the world continues to increase. The estimate 17 million deaths occur annually and are expected to continue to increase. In Indonesia, the prevalence of cardiovascular disease in 2018 reached 4.2 million. This high rate causes an increase in mortality so it is necessary to do prevention and control. Referring to the Ministry of Health's program, prevention and control of cardiovascular disease includes promotion efforts, risk prevention factors and disease management. Programs that are included in the minimum service standards in the health sector are risk factors for screening factors so that screening factor activities are important to carry out. Based on this, the Gatot Soebroto STIKes Community Service Team carried out a screening activity for cardiovascular disease risk factors which aimed to determine the presence of cardiovascular disease risk factors in 22 minisoccer players using survey and health examination methods. The results of the activity were that of the four risk factors that were examined, high blood pressure and overweight had the highest percentage compared to blood sugar and cholesterol examinations. The results of blood pressure measurements showed that 63.7% of respondents had pre-hypertension and hypertension, the majority of respondents (54.5%) were overweight, 95.5% of respondents with normal blood sugar and 72.7% of respondents with normal total cholesterol . From these results, it is necessary to carry out follow-up interventions to reduce blood pressure and BMI as an effort to prevent cardiovascular disease.